Blood Donation Tested by Coronavirus Pandemy 2019 (Covid-19) in Cote d’Ivoire - Kambe Kambé Yves; Hyda Jules; Diabate Songui (Britain International of Exact Sciences (BIoEx) Journal, 2021)
The 2019 coronavirus pandemic (covid-19), which spread rapidly around the world, has disrupted all organizations and led to a decline in their productivity. Their reorganization was therefore essential. The purpose of this study was to analyze the resilience strategies adopted by the National Blood Transfusion Service (NBTS) to reverse the trend of population participation. Thus, based on the qualitative approach centered on free interviews conducted with 30 people including 27 managers of Blood Transfusion Establishments (Blood Transfusion Center (BTC), Blood Transfusion Antenna (BTA) and Sampling Site (SS)), 2 heads of department (Communication and Coordination of services), the chairman of the scientific advisory council and a direct observation, of the theory of resilience and the systemic method, the analysis of the data indicates that the resilience strategies adopted by the NBTS are four: the dynamic communication on blood donation, rational blood using, the reorganization of blood collections in fixed site (Sundays and extension of the collection time) and the reorganization of mobile collections (fragmentation of mobile collection activities on site).